: سياسة الانتداب البريطاني على العراق 1920- 1932 - عماري فطيمة, عرجون سعدية (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2020)
تناولت الدراسة الموسومة بعنوان " سياسة الانتداب البريطاني على العراق 1920- 1932 الدخول البريطاني لبلاد مابين النهرين وفرض الانتداب عليها حسب مقررات مؤتمر سان ريمو. حيث تمّ التركيز على أهم الأحداث السياسية والمتمثلة في ثورة العشرين التّي تمخض عنها قيام الحكم الملكي وتنصيب فيصل الأول على العرش. كما شهدت الفترة ما بين 1922- 1932 مجموعة من المعاهدات بين بريطانيا والعراق، والتّي كان من شأنها أن تحقق لكل طرف مبتغاه فكانت المعاهدة الرابعة 1930 لصالح العراق حيث منحته الاستقلال وتمّ قبوله عضوا في عصبة الأمم 1932. The study concerns with The British Mandate policy for Iraq in the era of 1920 - 1932, by touching the British occupation for Mesopotamia with the beginning of World War I to the point of imposing the mandate as a result of the resolutions of San Remo conference of 1920. Where the interest was on the political events represented in the Iraqi revolt of 1920, which was considered an indication of the arrival of a new dawn in the future of Iraq, which resulted in the establishment of the monarchy and the inauguration of King Faisal I to the throne,by this step the British administration hope to restore its good reputation especially after its attitude on false promises towards Sharif Hussein. The era of 1922 - 1932 testify a series of treaties between Britain and Iraq that would achieve the
Keywords: الانتداب البريطاني- العراق--